2022
DOI: 10.1007/s00167-022-07196-9
|View full text |Cite
|
Sign up to set email alerts
|

Higher sensitivity and accuracy of synovial next-generation sequencing in comparison to culture in diagnosing periprosthetic joint infection: a systematic review and meta-analysis

Abstract: Purpose The purpose of this meta-analysis was to compare the diagnostic parameters of synovial next-generation sequencing (NGS) and cultures in diagnosing periprosthetic joint infections (PJI). Methods PubMed, Web of Science, Cochrane, and Google Scholar were searched from inception until 8 Jan 2022 for literature investigating the role of NGS in comparison to culture in the diagnosis of PJI. The studies were included if they investigated the diagnostic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The sensitivity and specificity of NGS for PJI diagnosis vary among different studies. The meta-analysis published by Hantouly et al reported a pooled sensitivity of 94%, higher than the one obtained by culture (70%) and slightly lower specificity (89%) in comparison to culture (94%) [46]. Additionally, the accuracy was higher using NGS technology (91.9%) than culture-based methods (80.5%).…”
Section: Next-generation Sequencing and Metagenomicsmentioning
confidence: 89%
“…The sensitivity and specificity of NGS for PJI diagnosis vary among different studies. The meta-analysis published by Hantouly et al reported a pooled sensitivity of 94%, higher than the one obtained by culture (70%) and slightly lower specificity (89%) in comparison to culture (94%) [46]. Additionally, the accuracy was higher using NGS technology (91.9%) than culture-based methods (80.5%).…”
Section: Next-generation Sequencing and Metagenomicsmentioning
confidence: 89%
“…Despite the culture‐negative rate (35.7% to 34.6% in the first DAIR vs. 46.2% in the unplanned second DAIR), our study was unable to definitively discern whether persistent infection, new infection, or a combination of both were present. Modern techniques with next‐generation sequencing [ 11 ] and machine‐learning model might be helpful in the future [ 18 ]. This limitation led us to implement a time interval of 2 years after the completion of antibiotic treatment to evaluate if a subsequent PJI occurred.…”
Section: Discussionmentioning
confidence: 99%
“…NGS techniques demonstrated, in previous studies, very high sensitivity and specificity in microorganism detection [ 4 , 7 , 13 ]. Nevertheless, a major limitation of the use of current NGS techniques in synovial fluid analysis is represented by the high incidence of detection of multiple microorganisms in the same synovial fluid sample: few authors utilized this finding to support the multi‐bacterial etiopathogenesis of many PJI [ 8 , 18 ] while other authors [ 27 ] considered those microorganisms as native microbiome rather than pathogenic microbes. In the current study, mNGS was the main determinant for microorganism detection in only 11%: this finding confirms previous recommendations that nucleic acid amplification techniques do not represent, so far, the first‐line diagnostic technologies for microorganism detection in SA and PJI scenarios [ 8 , 18 ] but a complementary tool to conventional culture and PCR assays [ 6 , 15 ].…”
Section: Discussionmentioning
confidence: 99%